PENGARUH LINGKUNGAN KERJA SOSIAL DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA PEGAWAI DI PT. INDUSTRI SUSU ALAM MURNI BANDUNG - Hari Mulyadi; Ridwan Purnama; Nopita Sukmawanti (Universitas Pendidikan Indonesia, 2021)
This research uses quantitative methods. Data collection using a questionnaire in the form of google form. The sample technique used is a saturated sample of 94 employees. The data analysis technique used is path analysis with SPSS version 25.0 computer software. The results of the research show that (1) The social work environment is at a fairly conducive level, (2) The physical work environment is at a good level, (3) Job satisfaction is at a very high level. (4) Social work environment have an effect of 0,413, (5) Physical work environment have an effect of 0,476, (6) The influence of social work environment and physical work environment on job satisfaction is 70.4%. When viewed from the Guilford table the effect of social work environment and physical work environment on job satisfaction is an very strong calassification. From the research results of hypothesis testing, it can be seen that social work environment and physical work environment have an effect on job satisfaction